iRGD-modified lipid–polymer hybrid nanoparticles loaded with isoliquiritigenin to enhance anti-breast cancer effect and tumor-targeting ability - Gao F (Dove Medical Press, 2017)
Fei Gao,1–3 Jinming Zhang,3 Chaomei Fu,3 Xiaoming Xie,4 Fu Peng,1–3 Jieshu You,1,2 Hailin Tang,1,2,4 Zhiyu Wang,5 Peng Li,6 Jianping Chen1–3 1School of Chinese Medicine, Li Ka Shing Faculty of Medicine, University of Hong Kong, Hong Kong, 2Shenzhen Institute of Research and Innovation, University of Hong Kong, Shenzhen, 3College of Pharmacy, Chengdu University of Chinese Medicine, Chengdu, 4Department of Breast Oncology, Sun Yat-Sen University Cancer Center, State Key Laboratory of Oncology in South China, Collaborative Innovation Center for Cancer Medicine, 5Department of Mammary Disease, Guangdong Provincial Hospital of Chinese Medicine, Guangzhou, 6State Key Laboratory of Quality Research in Chinese Medicine, Institute of Chinese Medical Sciences, University of Macau, Macau, People’s Republic of China Abstract: Isoliquiritigenin (ISL), a natural anti-breast cancer dietary compound, has poor delivery characteristics and low bioavailability. In order to promote the therapeutic outcome of ISL, a tumor-targeting lipid–polymer hybrid nanoparticle (NP) system modified by tumor-homing iRGD peptides has been developed. The hybrid NPs were prepared by a modified single-step nanoprecipitation method to encapsulate ISL. iRGD peptides were anchored on the surface by a postinsertion method (ISL-iRGD NPs). The stable lipid–polymer structure of ISL-iRGD NPs, with high encapsulation and loading efficiency, was confirmed. Compared to free ISL and non-iRGD-modified counterparts, ISL-iRGD NPs showed higher cytotoxicity and cell apoptosis against the different type of breast cancer cells. This was attributable to higher cellular accumulation mediated by the iRGD-integrin recognition and the nanoscale effect. More importantly, based on the active tumor-tissue accumulation by iRGD peptides and the prolonged in vivo circulation by the stealth nanostructure, ISL-iRGD NPs displayed higher tumor-growth inhibition efficiency in 4T1-bearing breast-tumor mouse models. Therefore, the constructed iRGD modified lipid–polymer hybrid NPs would provide a promising drug-delivery strategy to improve ISL in anti-breast cancer efficacy. Keywords: isoliquiritigenin, iRGD, lipid–polymer hybrid NPs, breast cancer